Brown tumor as an indication of a rare parathyroid carcinoma: A diagnostic challenge: Brown tumor reveals parathyroid carcinoma - Riaz, Noor; Lemmon, Lexington; Soubagle, Hamda; Marcelin, Necial; Masri, Mohammad (Journal of Surgery and Medicine, 2026)
Parathyroid carcinoma is an exceptionally rare cause of primary hyperparathyroidism, comprising less than 1% of cases. Its presentation often overlaps with benign etiologies, thereby posing significant diagnostic challenges. We present a case of a 70-year-old male with a history of prostate cancer who presented with profound hypercalcemia and markedly elevated parathyroid hormone. Imaging revealed lytic rib lesions consistent with osteitis fibrosa cystica (brown tumor). Surgical resection of a parathyroid mass confirmed parathyroid carcinoma. Postoperatively, the patient experienced symptomatic hypocalcemia due to non-adherence with calcium supplementation. This case highlights the need for clinical suspicion of parathyroid carcinoma in cases of severe hypercalcemia and skeletal manifestations and the importance of postoperative management in preventing complications such as hungry bone syndrome.